A Conceptualisation of the self-perceptions of black professionals in relation to business leadership in South Africa - Myeza, Angel (Graduate School of Business (GSB), 2022)
The research aimed to gain an understanding of the self-perceptions of black South African professionals (and leaders) in relation to business leadership and how these self-perceptions influenced their behaviours, aspirations and self-perceived abilities in leadership positions. The leadership behaviour of black leaders was found to be influenced by their upbringing, educational background, workplace experiences and the country's historical context. Leadership behaviours exhibited by black leaders included Ubuntu, difficulty with owning authority, deliberate bias in management behaviour across colour and a profound sense of shared responsibility toward other black professionals and black communities. Black professionals demonstrated signs of deep-rooted pain, fear, anger, isolation, pride, empathy and general emotional fatigue stemming from workplace, socio-economic and political triggers that evoked generational trauma and an overall negative black lived experience. The negative lived experience could have led to racial identity dissonance and in extreme cases, complete racial identity disassociation. On occasion, black professionals leveraged white relationships to propel their careers forward, however, this practice reportedly resulted in feelings of self-doubt. Self-doubt was shown to eventually lead to self-deselection, negatively impacting the aspirations and career advancement prospects of black professionals in organisational leadership. Career progression of black professionals was additionally impacted by 'multiple shades of black', which determined if the black professional could be 'authorised' as a leader. These 'shades' included aspects such as the 'twang', complexion, and for black women, even hair. Black professionals that were perceived to better resemble 'whiteness', achieved faster career progression. The research found that black leaders perceived that their blackness, specifically, its unique texture of experiences and history in South Africa, provided them with superior empathetic leadership capability towards black employees, although it severely diminished empathy towards white employees. Furthermore, black professionals considered their blackness to detract from their leadership capability, by reducing the odds of being authorised as a natural leader, enforcing a skewed self-perception of their leadership capabilities.